Reconstructive surgery options for elderly women with breast cancer. Clinical case - Ehrik K. Saribekyan; Elena A. Rasskazova; Umar Ibn Khomid Khomidi; ziz D. Zikiryakhodzhaev (LLC "MEDIAFORMAT", 2023)
The number of surgical interventions with a reconstructive component in elderly patients with breast cancer has been increasing over the recent years due to the development of reconstructive surgical techniques and anesthesia care improvement. Age is not an independent criterion allowing one to decide on the reconstruction feasibility, however, the algorithm of reconstructive option selection for this cohort of patients has some essential features.